2013
DOI: 10.1111/apa.12515
|View full text |Cite
|
Sign up to set email alerts
|

Respiration during sleep in children with therapy‐resistant enuresis

Abstract: We provide baseline data of nocturnal respiration in enuretic children. The children were found to have subclinical signs of disordered respiration. This may be one of the explanations for their high arousal thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…The results of the polysomnographic and otorhinolaryngologic baseline examinations of the studied children have been published separately . In short, we found that these children had more hypopneas and respiratory arousals than expected, as compared with published norms, an observation which led us to speculate that persistent arousal stimuli from partly obstructed airways may, via paradoxically increased arousal thresholds, be a pathogenetic factor underlying enuresis.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The results of the polysomnographic and otorhinolaryngologic baseline examinations of the studied children have been published separately . In short, we found that these children had more hypopneas and respiratory arousals than expected, as compared with published norms, an observation which led us to speculate that persistent arousal stimuli from partly obstructed airways may, via paradoxically increased arousal thresholds, be a pathogenetic factor underlying enuresis.…”
Section: Discussionmentioning
confidence: 47%
“…Baseline results for sleep variables and nasal airway patency data have been published separately . When relating response to RME therapy to polysomnographic data, no differences were found between the groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators have studied the relationship between enuresis and sleep disorders . Meanwhile, for some children, nocturnal enuresis is related with obstructive sleep apnea and subclinical signs of disordered respiration have been detected in enuretic children with no history of snoring . In contrast, sleep disorder could also affect memory .…”
Section: Discussionmentioning
confidence: 99%
“…24 Meanwhile, for some children, nocturnal enuresis is related with obstructive sleep apnea, 25 and subclinical signs of disordered respiration have been detected in enuretic children with no history of snoring. 26 In contrast, sleep disorder could also affect memory. 27,28 Regarding the relationship between PNE and sleep disorders with lower IQ scores in these children, it might be speculated that the lower IQ scores of children with PNE could be a consequence of the inferior sleep quality in these children.…”
Section: Discussionmentioning
confidence: 99%